A Candidate MEST Splice-Site Variant in a Patient with Silver–Russell Syndrome-like Phenotype: First Report and Literature Review - Xiaocha Xu; Rongrong Pan; Shuai Chen; Fan Yu; Haixia Miao; Kexin Fang; Dingwen Wu; Yi Zhang; Jing Li; Xin Yang (Genes, 2026)
Silver–Russell syndrome (SRS) is most commonly caused by epigenetic alterations at 11p15.5 or maternal uniparental disomy of chromosome 7 [upd(7)mat], though other molecular mechanisms remain unclear. While microdeletions encompassing MEST have been associated with SRS-like phenotypes, no pathogenic intragenic MEST variants have been reported to date. We describe a 6-month-old male infant with clinical features suggestive of a SRS-like phenotype, including intrauterine and postnatal growth restriction, triangular facies, prominent forehead, and small extremities. Methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) revealed neither methylation abnormalities at 11p15.5, 7p13, or 7q32 nor copy number variations (CNVs) in these regions. Trio whole-exome sequencing (trio-WES) identified a paternally inherited splice-site variant (c.890 + 1G > A) in MEST. Given the paternal-specific expression of MEST, this variant resides on the functionally active allele. Based on in silico predictions and clinical correlation, this case identifies MEST as a plausible candidate gene for SRS and provides a rationale for further functional studies. Phenotypic variation exists across molecular subtypes, yet definitive genotype–phenotype correlations await larger, systematically ascertained cohorts.